2012
DOI: 10.1111/j.1467-6494.2011.00748.x
|View full text |Cite
|
Sign up to set email alerts
|

The Hierarchical Structure of Childhood Personality in Five Countries: Continuity From Early Childhood to Early Adolescence

Abstract: Childhood personality is a rapidly growing area of investigation within individual differences research. One understudied topic is the universality of the hierarchical structure of childhood personality. In the present investigation, parents rated the personality characteristics of 3,751 children from 5 countries and 4 age groups. The hierarchical structure of childhood personality was examined for 1-, 2-, 3-, 4-, and 5-factor models across country (Canada, China, Greece, Russia, and the United States) and age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
145
0
12

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(180 citation statements)
references
References 62 publications
23
145
0
12
Order By: Relevance
“…Particularly, consistent with prior research on adolescent's peer-acceptance (Anderson et al, 2001;Mervielde & De Fruyt, 2000;van der Linden et al, 2010), the negative effects of Emotional Instability emerged over actual peer acceptance, but not over rejection, in both age groups. Because children high in Emotional Instability are characterized as being more tensed and anxious, such results point out once again that high level of this personality dimension can be considered a risk factor for school maladjustment.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Particularly, consistent with prior research on adolescent's peer-acceptance (Anderson et al, 2001;Mervielde & De Fruyt, 2000;van der Linden et al, 2010), the negative effects of Emotional Instability emerged over actual peer acceptance, but not over rejection, in both age groups. Because children high in Emotional Instability are characterized as being more tensed and anxious, such results point out once again that high level of this personality dimension can be considered a risk factor for school maladjustment.…”
Section: Discussionsupporting
confidence: 84%
“…Among these, those focusing on school-age samples have generally taken into consideration the positive pole of social status, which is represented by indices of acceptance (or likability) and popularity. Such investigations consistently suggest that peer social acceptance positively relates mainly to two dimensions, namely Extraversion and, to a less extent, Agreeableness (Jensen-Campbell et al, 2002;Lubbers, van der Werf, Kuyper, & Offringa, 2006;Mervielde & De Fruyt, 2000;van der Linden et al, 2010;Wolters, Knoors, Cillessen, & Verhoeven, 2013). Moreover, research on adolescent's peer-acceptance showed the negative effects of Emotional Instability over actual peer acceptance (Anderson et al, 2001;Mervielde & De Fruyt, 2000;van der Linden et al, 2010).…”
Section: Personality and Trait Emotional Intelligencementioning
confidence: 91%
See 2 more Smart Citations
“…Research has convincingly demonstrated that normal and abnormal personality are part of the same spectrum, and display a similar higher-order factor structure across age groups (22,(82)(83)(84)(85)(86)(87). However, Western folk psychology generally views children and adolescents as having personalities that are unstable or "under construction" whereas adult personalities are perceived as relatively unchanging (51,88).…”
Section: Continuity and Change In Personality Disordermentioning
confidence: 99%